1985
DOI: 10.1080/00268978500101591
|View full text |Cite
|
Sign up to set email alerts
|

Free energy functions in the extended RISM approximation

Abstract: It is shown that the free energies associated with the solutions of extended RISM integral equations can be obtained in closed form thus avoiding the necessity of numerical coupling parameter integrations. In addition, variational principles are deduced which provide a basis for efficient algorithms to solve extended RISM integral equations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
267
1

Year Published

1988
1988
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 344 publications
(273 citation statements)
references
References 5 publications
5
267
1
Order By: Relevance
“…The distribution functions predicted by the IEs can be used to describe much of the thermodynamics of the solution mixture but remain inherently approximate. Statistical thermodynamics provides convenient analytical expressions for the solution thermodynamics using the site-site distribution functions 43,44 . Some recent advances in IE theory offer more rigor and accuracy but have yet to be extended to aqueous systems 41 .…”
Section: Introductionmentioning
confidence: 99%
“…The distribution functions predicted by the IEs can be used to describe much of the thermodynamics of the solution mixture but remain inherently approximate. Statistical thermodynamics provides convenient analytical expressions for the solution thermodynamics using the site-site distribution functions 43,44 . Some recent advances in IE theory offer more rigor and accuracy but have yet to be extended to aqueous systems 41 .…”
Section: Introductionmentioning
confidence: 99%
“…Within the context of the extended RISM theory in conjunction with the HNC analogue closure equation, Singer and Chandler 45 have shown that the solvation free energy of a solute molecule at infinite dilution can be written in an analytical form and without integration over a coupling parameter . This solvation free energy expression is 46…”
Section: ͑7͒mentioning
confidence: 99%
“…Details of the theory are described in the literature. 9,10,45,46 Essentially, the RISM equation 11 is an Ornstein-Zernike-like relation between the site-site pair correlation functions h i j and the direct correlation functions…”
Section: B the Extended Rism Equationmentioning
confidence: 99%
“…Here H 0 is Fock operator in gas phase, ψ is the wave function of solute, and ∆µ is the excess chemical potential which is the functional of the solute-solvent total correlation function h(ω 1 ω 2 R 12 ) and the direct correlation function c(ω 1 ω 2 R 12 ) as well as the solute-solvent interaction energy u(ω 1 ω 2 R 12 ) [14];…”
Section: Moz-scf Formalismmentioning
confidence: 99%
“…An analytical expression of the free energy gradients in the RISM-SCF formalism was proposed by Sato et al [12,13]. They have reformulated the RISM-SCF equations with the use of the free-energy expression introduced by Singer and Chandler [14]. It has been shown that the derivation automatically provides variational conditions for multiconfigurational self-consistent-field (MCSCF) wave functions as well as the Hartree-Fock (HF) wave functions.…”
Section: Introductionmentioning
confidence: 99%